2020
DOI: 10.3389/fmicb.2019.03086
|View full text |Cite
|
Sign up to set email alerts
|

Ability of a Wild Weissella Strain to Modify Viscosity of Fermented Milk

Abstract: Despite the fact that strains belonging to Weissella species have not yet been approved for use as starter culture, recent toxicological studies open new perspectives on their potential employment. The aim of this study was to evaluate the ability of a wild Weissella minor (W4451) strain to modify milk viscosity compared to Lactobacillus delbrueckii subsp. bulgaricus, which is commonly used for this purpose in dairy products. To reach this goal, milk viscosity has been evaluated by means of two very different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…At low shear rate, the apparent viscosity decreased when increasing the shear rate in all cases (Figure 4). This flow is a typical shear-thinning and non-Newtonian behaviour, characteristic of pseudoplastic fluids, as reported by several authors for milks fermented with EPS-producing and non-producing LAB [61,62]. At higher shear rates, the viscosity decreased and remained without noticeable changes, then behaving as a Newtonian fluid [63].…”
Section: Characterization Of Skim Milks Fermented With the Eps-producsupporting
confidence: 77%
“…At low shear rate, the apparent viscosity decreased when increasing the shear rate in all cases (Figure 4). This flow is a typical shear-thinning and non-Newtonian behaviour, characteristic of pseudoplastic fluids, as reported by several authors for milks fermented with EPS-producing and non-producing LAB [61,62]. At higher shear rates, the viscosity decreased and remained without noticeable changes, then behaving as a Newtonian fluid [63].…”
Section: Characterization Of Skim Milks Fermented With the Eps-producsupporting
confidence: 77%
“…As shown in Table 1 , increasing the addition of EPS-YW11 from 0.25% to 1% ( w / v ) resulted in decreased hardness, adhesiveness and increased viscosity of the EPS-YW11/CAS complex samples, but cohesion of the samples were not obviously affected ( p > 0.05). This might be due to increased interactions of EPS with CAS when more EPS was added, leading to less hard and adhesive samples [ 35 , 36 , 37 ]. Previously, Zhang et al [ 38 ] reported that EPS could affect the textural properties of a yogurt clot by decreasing its hardness.…”
Section: Resultsmentioning
confidence: 99%
“…In certain cases, heat treatment is used to improve the EPS recovery from the culture medium as the first step in EPS isolation [ 27 , 32 , 35 , 58 , 97 , 98 ]. For the following precipitation of EPS, ethanol is commonly used [ 27 , 42 , 43 , 50 , 55 , 58 , 99 ], although isopropanol [ 100 ], acetone [ 33 ] or a mixture of acetone and ethanol [ 101 ] have been also used.…”
Section: Eps-producing Lactic Acid Bacteriamentioning
confidence: 99%
“…Finally, the EPS is lyophilized [ 27 , 33 , 35 , 43 , 99 , 101 ] to remove moisture and allow long storage. For molecular characterization purposes, additional purification steps have been employed to increase the purity of the EPS fraction, by applying advanced instrumental techniques such as size-exclusion chromatography (SEC) or ion-exchange chromatography [ 8 , 27 , 36 , 44 , 47 , 53 , 99 ].…”
Section: Eps-producing Lactic Acid Bacteriamentioning
confidence: 99%
See 1 more Smart Citation